Should We Extend Voluntary Euthanasia to Non-medical Cases? Solidarity and the Social Context of Elderly Suffering - Schmidt, Andreas T. (Journal of moral philosophy, 2020)
Several Dutch politicians have recently argued that medical voluntary euthanasia laws should be extended to include healthy elderly citizens who suffer from non-medical ‘existential suffering’ (‘life fatigue’ or ‘completed life’). In response, some seek to show that cases of medical euthanasia are morally permissible in ways that completed life euthanasia cases are not. I provide a different, societal perspective. I argue against assessing the permissibility of individual euthanasia cases in separation of their societal context and history. An appropriate justification of euthanasia needs to be embedded in a wider solidaristic response to the causes of suffering. By classifying some suffering as ‘medical’ and some as ‘non-medical’, most societies currently respond to medical conditions in importantly different ways than they do to non-medical suffering. In medical cases, countries like the Netherlands have a health care, health research and public health system to systematically assign responsibilities to address causes of medical suffering. We lack such a system for non-medical suffering among elderly citizens, which makes completed life euthanasia importantly different from euthanasia in medical cases. Because of this moral ‘responsibility gap’, focusing on the permissibility of completed life euthanasia in separation of wider societal duties to attend to possible causes is societally inappropriate. To spell out this objection in more philosophical terms, I introduce the concept of acts that are morally permissible but contextually problematic.